Managing Inclusive Early Childhood Education: Strategies and Challenges in Supporting Children with Special Needs - Abubakar, Sitti Rahmaniar; M., Sri Yuliani; Ashar, Dinar Salasatun (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
According to recent data, the number of children with special needs in Indonesia has reached 1,544,184, with 330,764 of these children (21.42%) aged 5–18 years. However, only 85,737 children with special needs are currently enrolled in school. This disparity highlights the urgent need for efforts to ensure that these children receive an appropriate education. The aim of this study is to analyze the management of inclusive Early Childhood Education (PAUD) in the context of inclusive education, focusing on the following aspects: first, the policies supporting inclusive education; second, the implementation of the inclusive education program; third, the challenges faced by educators and other stakeholders in implementing the program; and fourth, the outcomes achieved in improving access to appropriate education for children with special needs. The research adopts a qualitative approach with a case study design. Data collection methods include three primary techniques: interviews, observation, and documentation. The data were analyzed using the Miles and Huberman framework, which includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that the institution in question is committed to providing inclusive education for all children, including those with special needs. The school offers assistant teachers, therapy rooms, creative learning methods, and accessible facilities to support the learning process. Support from the government and related institutions plays a crucial role in improving educator competencies and expanding facilities, both of which are vital for the success of inclusive education programs. Abstrak: Menurut data terbaru, jumlah anak dengan kebutuhan khusus di Indonesia mencapai 1.544.184, dengan 330.764 anak (21,42%) berada dalam rentang usia 5–18 tahun. Namun, hanya 85.737 anak dengan kebutuhan khusus yang terdaftar di sekolah. Ketimpangan ini menunjukkan perlunya upaya untuk memastikan anak-anak tersebut menerima pendidikan yang sesuai. Tujuan dari penelitian ini adalah untuk menganalisis pengelolaan Pendidikan Anak Usia Dini (PAUD) inklusif dalam konteks pendidikan inklusif, dengan fokus pada aspek-aspek berikut: pertama, kebijakan yang mendukung pendidikan inklusif; kedua, pelaksanaan program pendidikan inklusif; ketiga, tantangan yang dihadapi oleh pendidik dan pihak terkait dalam melaksanakan program ini; dan keempat, hasil yang dicapai dalam meningkatkan akses pendidikan yang sesuai bagi anak-anak dengan kebutuhan khusus. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Metode pengumpulan data yang digunakan mencakup tiga teknik utama: wawancara, observasi, dan dokumentasi. Data yang dikumpulkan dianalisis menggunakan teknik analisis Miles dan Huberman, yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa institusi yang diteliti berkomitmen untuk menyediakan layanan pendidikan inklusif bagi semua anak, termasuk anak-anak dengan kebutuhan khusus. Sekolah ini menawarkan guru pendamping, ruang terapi, metode pembelajaran kreatif, dan fasilitas yang dapat diakses untuk mendukung proses pembelajaran. Dukungan dari pemerintah dan lembaga terkait sangat penting dalam meningkatkan kompetensi pendidik dan memperluas fasilitas, yang keduanya vital untuk keberhasilan program pendidikan inklusif.